Seasonality and host-parasite interrelationship of Hysterothylacium aduncum (Nematoda) in whiting Merlangius merlangus off the southern and northern coasts of the Black Sea - Özer A.; Kornyychuk Y. M.; Yurakhno V.; Öztürk T. (Helminthologia, 2016)
In the present study, we investigated the comparative infection levels, ecology and host-parasite interrelationship of a nematode Hysterothylacium aduncum (Rudolphi, 1802) in whiting, Merlangius merlangus (L., 1758) in southern (Sinop) and northern (Balaklava Bay) coasts of the Black Sea for the first time. Fish were collected throughout a period from May 2011 to March 2014 from local fishermen. A total of 690 fish specimens near Sinop and 423 fish near Balaklava Bay were examined for parasites. Hysterothylacium aduncum was the only nematode species identified in the digestive tract of the Black Sea whiting Merlangius merlangus. Prevalence of infection, mean intensity and mean abundance values were determined according to season, length classes and sex of fish at both localities. These infection indices were always higher in Sinop samples than those of Balaklava Bay samples.